2010
DOI: 10.1007/s12011-010-8912-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Selenium Source, Storage Time, and Temperature on the Quality of Quail Eggs

Abstract: We report the effects of time of storage, temperature, and supplementation with sodium selenite- and selenium-enriched yeast on the quality of quail eggs. For this study, 90 10-week-old female Japanese quails (Coturnix coturnix japonica) with similar body size were caged individually and randomly divided into five groups of 18 quails each. One group was fed a normal diet and served as control. A second group was supplemented with 0.2 mg/kg sodium selenite (In-Se) and three groups supplemented with 0.1, 0.2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…Supplementation of the diet with Se-yeast significantly affected egg weight, egg yolk and albumen weight as well as the Haugh units in eggs from Hy-Line Brown chickens [18]. Baylan et al also reported that the majority of indicators of egg quality are positively influenced by selenium yeast supplementation in Japanese quails [19].…”
Section: Introductionmentioning
confidence: 97%
“…Supplementation of the diet with Se-yeast significantly affected egg weight, egg yolk and albumen weight as well as the Haugh units in eggs from Hy-Line Brown chickens [18]. Baylan et al also reported that the majority of indicators of egg quality are positively influenced by selenium yeast supplementation in Japanese quails [19].…”
Section: Introductionmentioning
confidence: 97%
“…It has described that organic selenium supplementation in commercial poultry feeds has positive impact (ElSheikh & Ahmed-Nagwa 2006; Baylan et al 2010). The use of Se-enriched yeast in laying hen diets increases selenium content of egg (Utterback et al 2005;Gajcevic et al 2009;Attia et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Poor quality results in substantial economic losses to the worldwide egg industry. For example, losses due to poor eggshell quality have been Effects of Cage Stocking ... calculated to be in the order of 6-8% [3] . The egg industry is more dependent on high stocking densities for laying hens and quails either during the rearing or laying phases as a tool to reduce housing and equipment costs per bird.…”
Section: Introductionmentioning
confidence: 99%